The role of ventral tegmental area in chronic stroke rehabilitation: an exploratory study - Astrakas, Loukas G.; Elbach, Sabrina; Giannopulu, Irini; Li, Shasha; Benjafield, Howard; Tzika, A. Aria (Frontiers in Neurology, 2023)
The role of external rewards in chronic stroke rehabilitation is well-established, providing positive reinforcement and motivation for patients, fostering engagement and perseverance. However, the importance of self-reward remains largely unexplored. To investigate this, a study focused on the functional connectivity of the ventral tegmental area (VTA), a key hub in the reward brain circuitry, during motor task-based rehabilitation and its relation to the recovery process. Twelve right-handed healthy volunteers (4 men, 8 women, aged 57.4 ± 11.3 years) and twelve chronic stroke patients (5 men, 7 women, aged 48.1 ± 11.1 years) with clinically significant right-sided motor impairment (mean FM-UE score of 27.6 ± 8.7) were enrolled in this study. The analysis of psychophysiological interaction (PPI), as implemented in the CONN toolbox, assessed the association between motor tasks and the connectivity of reward areas. PPI analysis revealed motor-dependent changes in VTA connectivity with various regions within the motor circuitry, cerebellum, and prefrontal cortex. Stronger connectivity between the ipsilesional VTA and cerebellum was observed in healthy controls compared to chronic stroke patients, highlighting the significance of VTA-cerebellum interactions in Reward in stroke rehabilitation 2 motor function. Stroke patients' motor performance was associated with VTA modulation in areas related to motor tasks and reward processing, underscoring the relevance of self-reward processes in rehabilitation. Moreover, changes in VTA influence on motor circuitry were linked to improvements in motor performance resulting from rehabilitation. The findings demonstrate the potential of neuroimaging techniques to quantify and predict rehabilitation outcomes by examining self-reward processes, highlighting the importance of psychological factors in the rehabilitation process.